Effect of essential and non-essential amino acid supplementation in canine nutrition - Ayala-Limaylla, Frank (2023)
The study evaluated the effect of a nutritional supplement (composed of the 10 essential and eight non-essential amino acids) and a commercial vitamin supplement on body weight and body condition of 44 malnourished dogs (body condition 1 and 2). The animals were weighed and evaluated on days 1, 7 and 14 of treatment. All the dogs gained weight in the 14 days of the study; however, those treated with the supplement based on essential and non-essential amino acids showed greater weight gain compared to the group treated with the vitamin supplement (p<0.05).